The cost of constituent-rebalancing of Sharīʿah-compliant indexes: lessons for future crises - Ahmed Badreldin (ISRA International Journal of Islamic Finance, 2022)
Purpose - This study aims to quantify the cost of rebalancing Sharīʿah-compliant indexes, both economically and statistically. Design/methodology/approach - An empirical approach is employed where the rebalanced Sharīʿah-compliant index is calculated numerous times with different lags in rebalancing, and the number of stocks and their cost across time are determined in order to identify the optimal rebalancing frequency. Findings - This paper finds that annual Sharīʿah rebalancing does not lead to significant differences in portfolio returns, even though it does bring some advantages in cumulative wealth starting from the third year onwards and brings about better risk-return characteristics measured in terms of the Sharpe ratio. However, these advantages involve an average annual shifting between 30 and 60% of the portfolio market capitalization, which would be costly at any level of transaction costs. Practical implications - A private investor may be better off holding a constant portfolio and only rebalancing in three-year intervals since this was shown to possess similar portfolio returns and cumulative wealth results. Any advantages of annual rebalancing in terms of risk-return characteristics may be offset by transaction costs of rebalancing. Sharīʿah scholars and practitioners are to determine when the correct time for rebalancing really is, taking into consideration the cost of rebalancing vis-à-vis the advantages in cumulative wealth and risk-return characteristics of the portfolio. Originality/value - Predictions that Islamic indexes will perform well during financial crises, such as the COVID-19 pandemic, miss the cost of frequent rebalancing. This paper addresses this issue in an empirical manner learning from the previous crisis in 2008.
Keywords: 330; Financial crisis; Index constituents; Sharīʿah compliance